Rational and irrational factors that predict the continued intention to engage in digital reading: a perspective from China - Wu, Yun; Sun, Mengru (Malaysian Journal of Library and Information Science, 2022)
Few studies have examined factors, including irrational factors, that affect the continued intention of digital reading. This research attempts to propose an integrated framework to understand the continued intention to engage in digital reading. Based on weighted and calculated needs for new media and the technology acceptance model, the current research empirically investigated continued digital reading using an online survey. The research examined two rational factors—technology characteristics (perceived ease of use, perceived usefulness, and relative advantage) and individual motivations (perceived needs and perceived value)—as well as two irrational factors (emotional preference and perceived herd behaviour).This study found that the perceived ease of use and relative advantage of digital reading, as well as users’ perceived needs (information needs and social needs), perceived value (perceived benefits), and the irrational factor of perceived herd behaviour could predict the continued intention to read digitally. We provided a theoretical framework for understanding the mechanisms of the continued intention to engage in digital reading. The research provided theoretical and practical enlightenment for the development and promotion of digital reading.